Upaya Peningkatan Angka Penjualan Di Kelurahan Rungkut Kidul Melalui Program Pendampingan Digital Marketing UMKM Tahu Walik - Farastutie, Innike Fitra; Pratama, Rifqi Agata Geovani; Amin, Muhammad Arya Baharudin; Alhamdany, Savi Nadine Assalma; Rachman, Thoriq Firmansyah (Universitas Gajah Putih, Indonesia, 2023)
This research is a type of descriptive research that uses a qualitative approach. The data collection technique used by the researchers in this study is the interview. The interview was conducted by coming to the UMKM partners in the Kelurahan Rungkut Kidul where to know the progress of UMKM. Data used in the research can be obtained through recordings, records, library surveys, participation and interviews. In this study, the researchers used two types of data: secondary and primary data. In this study, the author will describe the results of the research already carried out. The results of the study are obtained from what is observed, felt, seen and questioned during the progress of the research carried out by the research object. This research is expected to describe the connection of various hat related to the question that will be explained about the knowledge of the people of Kelurahan Rungkut Kidul against the support of the UMKM and about the progress of UMKM. In this case, UMKM is one of several sectors that exist and has a very large impact and influences the era of digital technology development that is functioning for the marketing activities of various products that UMKM owns through containers or platforms that are digital one type of marketplace. The UMKM itself has a role that tends to be sufficiently extreme for it to trigger a strategic role in the Indonesian economy. Socialization of digital marketing strategies in the form of social media is very important because it can provide information to UMKM stakeholders regarding opportunities and steps to expand consumer networks through social media to market their products so as to increase the competitive advantage of the UMKM themselves.